The Global Burden of Osteoporosis, Low Bone Mass, and Its Related Fracture in 204 Countries and Territories, 1990-2019 - Shen, Yuyan; Huang, Xin; Wu, Junyun; Lin, Xiling; Zhou, Xiao; Zhu, Zhiang; Pan, Xiaowen; Xu, Jingya; Qiao, Jie; Zhang, Tianyue; Ye, Linxia; Jiang, Hongwei; et al. (Frontiers in Endocrinology, 2022)
Background: Low bone mineral density (LBMD), including osteoporosis and low bone mass, has becoming a serious public health concern. We aimed to estimate the disease burden of LBMD and its related fractures in 204 countries and territories over the past 30 years. Methods: We collected detailed information and performed a secondary analysis for LBMD and its related fractures from the Global Burden of Disease Study 2019. Numbers and age-standardized rates related to LBMD of disability-adjusted life-years (DALYs) and deaths in 204 countries and territories were compared by age, gender, socio-demographic index (SDI), and location. Results: Global deaths and DALYs number attributable to LBMD increased from 207367 and 8588936 in 1990 to 437884 and 16647466 in 2019, with a raise of 111.16% and 93.82%, respectively. DALYs and deaths number of LBMD-related fractures increased 121.07% and 148.65% from 4436789 and 121248 in 1990 to 9808464 and 301482 in 2019. In 2019, the five countries with the highest disease burden of DALYs number in LBMD-related fractures were India (2510288), China (1839375), United States of America (819445), Japan (323094), and Germany (297944), accounting for 25.59%, 18.75%, 8.35%, 3.29%, and 3.04%. There was a quadratic correlation between socio-demographic index (SDI) and burden of LBMD-related fractures: DALYs rate was 179.985-420.435SDI+417.936SDI2(R2=0.188, p<0.001); Deaths rate was 7.879-13.416SDI+8.839 SDI2(R2=0.101, p<0.001). Conclusions: The global burden of DALYs and deaths associated with LBMD and its related fractures has increased significantly since 1990. There were differences in disease burden between regions and countries. These estimations could be useful in priority setting, policy-making, and resource allocation in osteoporosis prevention and treatment.